2011
DOI: 10.1158/0008-5472.can-10-1874
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin Induces Irreversible Mitotic Blockade: Implications of Cell-Based Pharmacodynamics for In vivo Efficacy under Intermittent Dosing Conditions

Abstract: Eribulin (E7389), a mechanistically unique microtubule inhibitor in phase III clinical trials for cancer, exhibits superior efficacy in vivo relative to the more potent compound ER-076349, a fact not explained by different pharmacokinetic properties. A cell-based pharmacodynamic explanation was suggested by observations that mitotic blockade induced by eribulin, but not ER-076349, is irreversible as measured by a flow cytometric mitotic block reversibility assay employing full dose/response treatment. Cell via… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 19 publications
(26 reference statements)
3
110
0
3
Order By: Relevance
“…4-6). 20 Unfortunately, there is no clear indication to what extent cellular persistence is a desirable property for a drug. The relative reversibility of a compound does not often factor into cellular assays where the cells are constantly bathed in drug-containing media.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 1 more Smart Citation
“…4-6). 20 Unfortunately, there is no clear indication to what extent cellular persistence is a desirable property for a drug. The relative reversibility of a compound does not often factor into cellular assays where the cells are constantly bathed in drug-containing media.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Clinically used drugs, including vincristine and eribulin, demonstrate a high degree of cellular persistence. 20 In contrast, the cellular effects of both paclitaxel and vinblastine, which are also clinically valuable microtubule targeting agents, are less persistent. 20 Further analysis of the relationship between in vitro reversibility and clinical efficacy may be valuable to identify whether there is a link between these factors.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Gajate and colleagues (48) reported that cells treated with the bicyclic colchicine analogue MCT for a short period of time (before induction of the apoptotic response) resumed proliferating; however, once the treatment period exceeded the tolerable threshold (cell line specific) and apoptosis was triggered, the cell proliferation capacity could not be restored by the removal of the inhibitor. Furthermore, Towle and colleagues showed that after 12 hours of treatment of U-937 cells (histiocytic lymphoma) with microtubule-targeting agents at concentrations that induced complete mitotic block, and 10 hours of washout, the mitotic arrest was reversible or irreversible depending on the compound (38). Small changes in chemical structures between analogues (e.g., eribulin vs. ER-076349, vincristine vs. vinblastine, colchicine vs. colcemid) led to profound differences in mitotic block reversibility.…”
Section: Discussionmentioning
confidence: 99%
“…A clonogenic assay was used to evaluate the ability of polygamain to inhibit colony formation of PC-3 cells after a 12-h exposure to the IC 50 concentration. Notable differences in cellular persistence have recently been noted among compounds representing diverse classes of microtubule-disrupting agents Towle et al, 2011). The effects of polygamain in this assay were compared with the effects of podophyllotoxin and CA-4.…”
Section: Isolation Of Polygamain and Evaluation Of Its Microtubule Anmentioning
confidence: 99%